Reduction of hyperoxic acute lung injury in mice by Formononetin - Chen, Yin (PLoS One, 2021)
BACKGROUND: The antioxidant and anti-inflammatory features of Formononetin, an isoflavone constituent extracted from traditional Chinese medicine, have been reported. The present study investigated that whether Formononetin plays a benefit on hyperoxic ALI. METHODS: C57BL/6 mice were exposed to hyperoxia for 72 h to produce experimental hyperoxic ALI model. Formononetin or vehicle was administrated intraperitoneally. Samples from the lung were collected at 72 h post hyperoxia exposure for further study. Pulmonary microvascular endothelial cells isolated from the lung of C57BL/6 mice were used for in vitro study. RESULTS: Formononetin pretreatment notably attenuated hyperoxia-induced elevating pulmonary water content, upregulation of proinflammatory cytokine levels and increasing infiltration of neutrophil in the lung. Western blot analyses showed that Formononetin enhanced the expression of nuclear factor erythroid-2-related factor 2 (Nrf2) which is a key transcription factor regulating the expression of heme oxygenase-1 (HO-1). Formononetin increased HO-1 expression and activity compared with vehicle-treated animals. Moreover, Formononetin reversed hyperoxia-caused the reduction of M2 macrophage polarization. However, pretreatment of a HO-1 inhibitor reduced the protective effect of Formononetin on hyperoxic ALI. Cell study showed that the Formononetin-induced upregulation of HO-1 was abolished when the Nrf2 was silenced. CONCLUSIONS: Formononetin pretreatment reduces hyperoxia-induced ALI via Nrf2/HO-1-mediated antioxidant and anti-inflammatory effects.